Differential Susceptibility of Diverse Salix spp. to Melampsora americana and Melampsora paradoxa - Crowell, Chase R (Plant disease, 2020)
Melampsora spp. willow rust is the most serious disease of shrub willow bioenergy production in the northeastern United States. Recent phylogenetic studies have identified several Melampsora spp. present on willow in the Northeast; however, in-depth understanding of Melampsora spp. host susceptibility remain unresolved. In this study, a panel of 82 rust isolates collected from the northeastern United States were genotyped via ribosomal DNA sequencing and a subset of these isolates were assayed for host susceptibility. This work revealed that Melampsora americana is the most prevalent species in the sampled geographic region and that there is potential for rust resistance breeding using the Salix spp. taxa assayed. Additionally, leaf morphology traits of these Salix spp. hosts were quantified for correlation analysis, revealing that trichome density and stomata density are possible contributors to resistance. This work provides foundational rust pathology information, which is crucial for M. americana resistance breeding